Growth and yield responses of chickpea var. BARI chola-7 following application of TIBA - Islam, Saiful; Jahan, Nargis (Bangladesh Journal of Botany, 2019)
A field experiment was conducted to evaluate the effect of TIBA (0, 10, 20, 50 and 100 ppm) on the growth and yield attributes of BARI Chola-7 laid out in RBD. Foliar application of TIBA at flower initiation stage, decreased plant height significantly with increasing concentrations of TIBA. Number of branches and leaves per plant were found to increase from 21 and 14 days after spray (DAS) onwards, respectively due to all the TIBA treatments and the maximum number of branches and leaves per plant were recorded due to 100 ppm TIBA which was statistically at par with 20 and 50 ppm TIBA. Dry matter per plant was recorded maximum from 21 DAS up to harvest due to 20 ppm TIBA. Except 100-seed weight, other yield contributing characters viz. number of seeds per plant, yield per plant, yield per hectare were also found to maximum due to 20 ppm TIBA treatment. The highest harvest index was recorded from 20 ppm TIBA.